(untitled) (Baghdad Science Journal, 2023)
The objective of this study was to isolate and identify the asparaginase-producing bacteria, then purify and characterize the enzyme in order to investigate their properties in the future. Fifteen local bacterial isolates were isolated from various sites in the city of Baghdad, identified by conventional morphological and biochemical procedures, and confirmed using vitek 2 methods, and submitted to primary screening processes for asparaginase production. For secondary screening, eight isolates with the greatest yellow zone ability on a specific solid medium were chosen. Bacillus sp. was reported to have the highest enzyme production (7.5 U/mg proteins). After 24 hours of incubation, submerged fermentation yielded optimal conditions for the production of L-asparaginase (L-ASNase) by the chosen isolate, with medium (2) serving as the optimal medium for production and fructose serving as the optimal source of carbon. In pH 6 at 40°C, Sephadex G-150 gel filtration chromatography was used to purify the enzyme. The final purification folds were increased by 2.5 times, resulting in an enzyme yield of 93.7%. It also showed the highest purified enzyme activity and stability was at 37°C. Also it revealed the highest activity and stability at pH 7.0 and pH 8.0 respectively. Enzyme lost activity when exposed to several metallic ions at concentrations of 1, 5, and 10 mM.